Effect of Pregabalin on the Median Effective Plasma Concentration of Intravenous Alfentanil in Capsaicin-Induced Pain. Issue 12 (30th July 2021) - Wallace, Mark S
Abstract: Objective: To apply the sequential up–down method to a human experimental pain model in order to examine the opioid-sparing effect of oral pregabalin on intravenous alfentanil. Design: Double-blind, randomized, crossover. Setting: Academic university medical center. Subjects: Thirty-one healthy males. Methods: The median effective plasma concentration of intravenous alfentanil was determined under two conditions: alfentanil alone (phase I) and alfentanil+ pregabalin (300 mg orally) (phase II). The alfentanil plasma level (after a computer-controlled infusion) producing a success criterion (at least 30% intradermal capsaicin-induced pain reduction compared with placebo) was used to determine higher or lower doses for each sequential subject. The median dose producing a success criterion and its confidence interval were determined. Results: On the basis of the t test for a difference across phase and regression coefficients across groups, there was no opioid-sparing effect of pregabalin on alfentanil. Four subjects in phase I and five subjects in phase II did not complete the study. Two in phase I were technical failures, with the rest in both phases stopped because of side effects. Of the subjects who completed the study, six of 19 subjects in phase I and 11 of 12 subjects in phase II reported side effects. Conclusions: When the intradermal capsaicin-induced pain model was used in healthy volunteers, oral pregabalin had no opioid-sparing effects on intravenous alfentanil. This experimental model may be useful in studying analgesic interactions.